Introduction - Fluckiger, Cédric; Boulc'h, Laetitia; Nogry, Sandra; Reffay, Christophe (Enseigner, apprendre, former à l’informatique à l'école : regards croisés, 2025)
This book is the result of an ANR project, "IE-CARE", aimed at understanding and proposing sustainable conditions and modalities for teaching computer science in compulsory schools. To understand the conditions for teaching computer science, it brings together eleven contributions focusing on three fundamental processes: teaching (on the part of teachers), learning (for students) and training (for teachers).